Associations between implementation characteristics and evidence-based practice sustainment: a study of the Adolescent Community Reinforcement Approach. (December 2015) - Hunter, Sarah; Han, Bing; Slaughter, Mary; Godley, Susan; Garner, Bryan
Abstract Background Few empirical studies longitudinally examine evidence-based practice (EBP) sustainment and the hypothesized factors that influence it. In an effort to address this gap, the current study examined sustainment of an EBP for adolescent substance use called the adolescent community reinforcement approach (A-CRA). Methods A-CRA sustainment was assessed via information collected as part of key informant interviews and surveys with clinical staff from community-based treatment organizations that had received federal funding to implement A-CRA. Administrative data from the funding period on implementation was also used. Using discrete-time survival analysis, we regressed A-CRA sustainment on several factors theorized to influence EBP sustainment. Factors examined included outer setting, inner setting, implementation quality during the funding period, and intervention-related characteristics. Results Overall, data from 83 % of the targeted sample of treatment organizations was collected. A-CRA sustainment was strongly related to the time since funding loss. Strong relationships were found between sustainment status and implementation quality during the funding period, agency focus, funding stability, and political support for the treatment along with staff perceptions of the treatment's complexity and implementation difficulty. Conclusions Consistent with the Consolidated Framework for Implementation Research, the current study found several factors related to the outer setting (e.g., funding stability), inner setting (e.g., agency focus), implementation quality during the funding period (e.g., staff trained, clients served), and characteristics of the intervention (e.g., implementation complexity) to be associated with EBP sustainment. Future research is warranted to examine the extent to which these relationships are stable over time. Efforts to ensure that adequate implementation occurs during the initial implementation period and that adequate funding, infrastructure, and staff support following the ending of initial support are critical to a program's survival.